Peningkatan Aktivitas Pembelajaran dan Hasil Belajar Visual Merchandising Melalui Metode Penyelesaian Masalah: Improved Learning Activities and Learning Results Visual Merchandising Through Problem Resulution Methods - Abidin, Zainal (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to improve learning activities and learning outcomes for visual merchandising through problem solving methods. This research uses action research with a cycle of three times. Each cycle consists of four stages: design, activity and observation, reflection, and refission. The subject of this research is the students of class XI Data Marketing. From the results of the analyst found that student achievement has increased from cycle I to cycle III. Cycle I 64.00%, cycle II 76.00%, cycle III 88.00%. The conclusion of this study is that the problem solving method can positively influence the activities and learning outcomes of Class XI Marketing Students in Visual Merchandising subjects.